Gambaran Perilaku Judi Online pada Dewasa Awal di Kelurahan Alak Kota Kupang - Juan Valentino Bey; Dian L. Anakaka; Marleny P. Panis (Observasi : Jurnal Publikasi Ilmu Psikologi, 2026)
The rapid development of digital technology has increased public access to online gambling platforms, creating various psychological and social challenges, particularly among early adults. This study aimed to explore online gambling behavior among early adults in Alak Village, Kupang City. A qualitative approach with a descriptive design was employed. Three early adult participants who were actively involved in online gambling activities were selected purposively based on the study criteria. Data were collected through in-depth interviews and analyzed using Thematic Analysis. The findings revealed three major themes: the initial process of involvement in online gambling, patterns of gambling engagement, and emotional experiences during gambling activities. Initial involvement was influenced by social environments, attraction to others’ gambling winnings, and feelings of boredom and stress. All participants remained actively involved in online gambling, with online slot games being the most frequently played form. Furthermore, gambling wins generated positive emotional experiences that reinforced continued participation, whereas losses resulted in stress, disappointment, and psychological distress. These findings indicate that online gambling behavior is a multidimensional phenomenon shaped by the interaction of social, emotional, and cognitive factors.